The History and Future of Anticipatory Democracy and Foresight. (September 2019) - Bezold, Clem
Anticipatory democracy involves enhanced participation in shaping the future. Foresight involves applying futures tools to decision making. The Institute for Alternative Futures (IAF) over its four decades of work with communities, governments, and companies has evolved its "aspirational futures" approach that calls for creating expectable, challenging, and visionary scenarios and using these to enhance vision and the creation of preferred futures. Jim Dator's approach to scenario development was IAF's starting place. IAF has supported foresight in executive, legislative, and judicial branches of government, with the largest companies and nonprofit organizations, across six continents. Humanity is maturing, and the values of equity and inclusion are rising globally. Economies are transforming, including major job loss to automation and "abundance advances" technologies that provide low cost energy, 3D printing and local manufacturing, and home and community food production that have the potential to lower the cost of living. Foresight must be applied to understand and help create equitable and sustainable futures using these abundance advances in a transformed economy.